Pembuatan Bibliografi Beranotasi Koleksi Minangkabau di Pusat Dokumentasi Informasi Kebudayaan Minangkabau (PDIKM) Padang Panjang - Yarnita, Desi; Nelisa, Malta (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2013)
TheÂ purposes of this study were to: (1) describe a collection of annotated bibliography creation Minangkabau in Minangkabau Cultural Information Documentation Centre (PDIKM) Padang Panjang, (2) explain the constraints faced in making an annotated bibliography. Writing this paper uses descriptive research method. Stage of making a bibliography is: (1) determination of the title bibliography, (2) the collection of books, (3) the selection of library materials, (4) grouping or classification, (5) keyword generation, (6) preparation of the index, (7) the manufacture or manuscript typing bibliographies, (8) examination of the final manuscript. In making this bibliography, there are several constraints such as: (1) language books in Dutch, so it is difficult to understand the contents of the book, (2) there is a collection of old collection, so no information is lost because the writing was already fading. Keywords: annotated bibliography; Minangkabau collection Â